Increased Uptake of AV-1451 in a Subacute Infarction Lesion - Cho, Soo Hyun (Yonsei Med J, 2018)
(18)F-AV-1451 is a tau PET ligand that has high affinity for paired helical filament tau. However, various off-target bindings unrelated to tau have also been reported. Herein, we report a case of 83-year-old woman, who showed abnormal uptake of AV-1451 that was shown to be subacute infarction. Clinicians should recognize that increased uptake of AV-1451 may be related to stroke.